2017
DOI: 10.4049/jimmunol.1601477
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell–Derived IL-32α: A Novel Inhibitory Cytokine of NK Cell Function

Abstract: Cytokines produced by dendritic cells (DCs) can largely determine the direction of immunity. Transcriptional analysis revealed that besides IL-15, IL-32 was the only other cytokine expressed by human Langerhans cells. IL-32 is a human cytokine that exists in four main isoforms. Currently, little is known about the regulation and function of the various IL-32 isoforms. In this study, we found that IL-15 is a potent inducer of IL-32α in DCs. Because IL-15 promotes NK cell activation, we investigated the interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…Although IL-32β is known to present proinflammatory properties [43], it has been shown that IL-32β induces IL-10 production [62]. IL-32α is regarded as anti-inflammatory member of the IL-32 family which is able to inhibit NK cell activation and JAK/STAT pathway [63]. Thus, in our study all three isoforms are associated with proinflammatory cytokines in ATL, it is possible that IL-32β and IL-32α act as anti-inflammatory mediators in the lesions, being important to decrease the inflammatory process, however, whether IL-32β or IL-32α acts as an anti-inflammatory mediators in lesions of ATL patients is not known at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-32β is known to present proinflammatory properties [43], it has been shown that IL-32β induces IL-10 production [62]. IL-32α is regarded as anti-inflammatory member of the IL-32 family which is able to inhibit NK cell activation and JAK/STAT pathway [63]. Thus, in our study all three isoforms are associated with proinflammatory cytokines in ATL, it is possible that IL-32β and IL-32α act as anti-inflammatory mediators in the lesions, being important to decrease the inflammatory process, however, whether IL-32β or IL-32α acts as an anti-inflammatory mediators in lesions of ATL patients is not known at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that IL‐32‐specific siRNA in KCs strongly inhibited IL‐32 expression and consequently LC activation. While our manuscript was under review, Gorvel et al . showed that LCs expressed IL‐32 while in a ‘steady state’.…”
Section: Discussionmentioning
confidence: 99%
“…However, the method they used for LC isolation is quite different from ours. Gorvel et al . isolated LCs following 48 h of migration outside the skin, in contrast to the enzymatic digestion of skin cells used in our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IL-32 mRNA is highly expressed in immune cells, and IL-32 expression has also been detected in nonimmune tissues and cells [ 6 , 55 , 62 ]. NK cells [ 2 , 3 , 63 ], monocytes/macrophages [ 3 , 62 , 64 ], dendritic cells (DCs) from PBMCs [ 58 , 62 , 65 ], neutrophils [ 66 ], T lymphocytes [ 62 ], epithelial cells [ 67 ], endothelial cells [ 68 ], fibroblasts [ 69 ], and hepatocytes [ 64 ] can express IL-32. IL-32 is also expressed and released in both cancer and noncancer cell lines, including the HepG2 human cancer cell line [ 3 , 70 ], A549 cells [ 71 , 72 ], pancreatic cancer cell lines such as MIA PaCa-2, PANC-1, and BxPC-3 [ 73 , 74 ], the human hepatoma cell line Huh-7.5 [ 64 ], cervical cancer cells and tissues [ 75 ], the HEK293T cell line [ 34 , 57 ], the HT-29 human colon cell line [ 60 ], the human colon neuroendocrine LCC-18 cell line [ 34 ], human colonic subepithelial myofibroblasts [ 51 ], human primary keratinocytes [ 50 ], synovial cells and fibroblast-like synoviocytes (FLS) [ 14 , 69 ], and the marrow stromal cell lines HS-5 and HS-27A [ 76 ].…”
Section: The Cellular Source and Expression Of Il-32mentioning
confidence: 99%